Thiol modified nickel MOF nanosheet array material as well as preparation method and application thereof
By introducing thiol groups into the nickel MOF nanosheet array material, NiBDC@NiS0.68 material was prepared, which solved the conductivity and stability problems of existing nickel MOF materials in electrocatalytic applications, and achieved higher catalytic activity and efficiency.
Patent Information
- Application Number
- CN202510039645.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-05-16
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The existing nickel MOF nanosheet array materials have problems in electrocatalytic applications such as poor conductivity, poor structural stability, large ion diffusion resistance and limitations in alcohol oxidation reaction.
By introducing thiol groups into the nickel MOF nanosheet array material, a thiol-modified nickel MOF nanosheet array material (NiBDC@NiS0.68) was prepared, and the in-situ growth was adopted on the nickel foam surface using hydrothermal conditions to optimize the structure and electronic structure of the material.
It significantly improves catalytic activity and efficiency, enhances the adsorption capacity of the reaction intermediate, improves the stability and conductivity of the material, and enables it to show higher catalytic performance in alcohol oxidation reaction.
Smart Images

Figure CN120006344A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a thiol-modified nickel MOF nanosheet array material, a preparation method and an application thereof. Background Art
[0002] Global concern about plastic waste has intensified in recent years due to the continued accumulation of plastic waste in landfills and natural environments. The significant increase in plastic production and relatively low recycling rates have exacerbated the problem, making plastic pollution a pressing environmental challenge. Addressing this issue requires innovative solutions that not only reduce waste but also transform these discarded materials into valuable products. Among potential approaches, electrocatalytic recycling has emerged as a promising strategy, especially in the context of converting plastic waste into high-value chemicals. This approach uses renewable electricity to drive the transformation of waste, which is consistent with sustainable development goals by minimizing environmental impact.
[0003] Polybutylene succinate (PBS), a biodegradable polymer derived from succinic acid (SA) and 1,4-butanediol (BDO), is an alternative to traditional petroleum-based plastics. To reduce the carbon footprint of plastic disposal, an effective PBS recycling pathway is essential. Electrocatalytic recycling offers the potential to break down PBS into monomers or other valuable chemicals, providing a unique approach to convert biodegradable plastics into value-added chemicals, creating a closed-loop system. Among the potential products, SA is a key product in the process and has a wide range of industrial applications in biodegradable plastics, pharmaceuticals, and food additives. The development of efficient electrocatalytic systems to recycle PBS into high-purity SA is critical to ensuring a more sustainable life cycle for plastic materials.
[0004] The main defects of nickel MOF nanosheet array materials include low electrical conductivity, poor structural stability, large ion diffusion resistance, and specific limitations in alcohol oxidation reactions. Since the organic ligands and metal nodes of the MOF material itself usually cannot provide efficient electron transfer paths, its conductivity in electrochemical applications is limited. At the same time, it is easy to collapse or dissolve in the structure under long-term use or extreme environments (such as high temperature and high potential), affecting the catalytic activity. In addition, although the high specific surface area and porous structure are conducive to the adsorption of reactants, the larger pore distribution will also increase the ion diffusion resistance and reduce the overall catalytic performance. In the alcohol oxidation reaction, nickel MOF materials may show insufficient adsorption capacity for reaction intermediates (such as aldehydes or carboxylic acids), resulting in problems such as limited reaction paths and reduced utilization of active sites. These defects need to be solved by doping conductive materials, optimizing structural design, enhancing the catalytic ability of intermediates, or introducing more stable ligands. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of poor conductivity and low reaction activity in the above-mentioned prior art and to provide a thiol-modified nickel MOF nanosheet array material and a preparation method and application, thereby improving the catalytic activity of the MOF nanosheet array material and then improving the catalytic efficiency, thereby effectively catalyzing the oxidation of 1,4-butanediol and PBS plastic hydrolysate.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing a thiol-modified nickel MOF nanosheet array material, comprising mixing nickel salt, terephthalic acid, 1,4-benzenedimethanethiol and a solvent to obtain a reaction solution; immersing nickel foam in the reaction solution for a hydrothermal reaction, and obtaining NiBDC@NiS loaded on the nickel foam after the reaction is completed. 0.68 , that is, thiol-modified nickel MOF nanosheet array material.
[0008] Furthermore, the mass volume ratio of the nickel salt, terephthalic acid, 1,4-benzenedimethylenethiol and solvent is 25-40 mg: 15-25 mg: 2 mg: 1-5 mL, preferably 30-35 mg: 15-20 mg: 2 mg: 2-5 mL, and more preferably 33-35 mg: 18-20 mg: 2 mg: 3-5 mL.
[0009] Furthermore, the nickel salt includes nickel chloride, nickel sulfate and nickel nitrate.
[0010] Furthermore, the solvent is a N,N-dimethylformamide (DMF) mixed solution, which is a mixture of DMF, water and ethanol, and the volume ratio of the three is 10-20:1:0.5-2, preferably 14-18:1:0.8-1.2.
[0011] Furthermore, the mass volume ratio of the nickel foam to the reaction solution is 10-30 mg:1 mL.
[0012] Furthermore, the temperature of the hydrothermal reaction is 120-180° C., preferably 140-160° C.; the time of the hydrothermal reaction is greater than or equal to 6 hours, preferably 6-10 hours.
[0013] The second technical solution of the present invention is to provide a thiol-modified nickel MOF nanosheet array material, which is prepared by the preparation method.
[0014] Furthermore, the nickel MOF material is loaded on nickel foam and presents a nanosheet structure, wherein the nanosheet is loaded with nickel sulfide clusters.
[0015] The third technical solution of the present invention is to provide a thiol-modified nickel MOF nanosheet array material for use in the field of electrocatalysis.
[0016] Furthermore, the nickel MOF nanosheet array material is used as a catalyst for the reaction of oxidizing and catalyzing the hydrolysis product of PBS and BDO to generate succinate.
[0017] Furthermore, the hydrolyzate of PBS includes 1,4-butanediol and succinic acid.
[0018] Compared with the prior art, the present invention has the following advantages:
[0019] (1) In the nickel MOF nanosheet array material prepared in the present invention, MOF has the characteristics of large specific surface area, adjustable porosity, and rich active sites, which can improve the catalytic activity of the oxidation reaction and is a promising catalyst. The introduction of S optimizes the adsorption and local microenvironment of the reaction intermediates by modifying the electronic structure of the metal center, further improving the efficiency and stability of the catalyst. This makes the nickel MOF nanosheet array material show great prospects in alcohol oxidation reactions and become an ideal candidate for electrocatalytic processes, which is crucial for converting PBS-derived intermediates into SA.
[0020] (2) The present invention uses nickel salt as a metal salt driver, terephthalic acid as an organic ligand, and 1,4-benzenedimethanethiol as a modifier to in situ grow a nickel MOF nanosheet array material on the surface of nickel foam under hydrothermal conditions, namely NiBDC@NiS 0.68 The NiBDC@NiS prepared by the present invention 0.68 The randomly oriented nanosheet morphology of NiBDC is maintained, which is beneficial to accelerate the diffusion mass transfer of the catalytic reaction, accelerate the rapid desorption of accumulated bubbles, and have a large specific surface area, so that the active sites are fully exposed and the reaction kinetics are improved, making NiBDC@NiS 0.68 Compared with the precursor NiBDC, it is easier to adsorb 1,4-butanediol molecules.
[0021] (3) The present invention accelerates electron transfer by introducing S, increases the rate of transfer of reactants to the catalyst surface, and adjusts the position of the d-band center, thereby improving the catalytic performance of 1,4-butanediol oxidation.
[0022] (4) The present invention adopts an in-situ growth strategy to avoid the use of adhesives, ensuring that the NiBDC@NiS grown in situ 0.68 The close contact with the conductive substrate interface during application exposes more active sites, promotes the affinity between the catalyst and the reaction substrate, exposes more active sites, promotes the transfer of charges, and thus is beneficial to NiBDC@NiS 0.68 catalytic activity.
[0023] (5) NiBDC@NiS prepared by the present invention 0.68 It can effectively electrocatalyze the oxidation reaction of 1,4-butanediol, and achieve effective catalytic oxidation of 1,4-butanediol and PBS plastic hydrolysate at the anode under relatively low voltage input, thus efficiently producing high value-added succinate.
[0024] (6) The nickel MOF nanosheet array material prepared by the present invention has a higher specific surface area and active site utilization rate than conventional nickel MOF nanosheet catalysts. Its two-dimensional nanosheet array structure significantly improves the mass transfer efficiency. The nickel center metal provides excellent catalytic activity through redox cycles, and the introduction of S enhances conductivity and catalytic performance through electronic structure regulation. During the preparation process, nickel salt provides active centers, ligands form stable skeletons, thiols introduce functionalization, solvent systems and solvothermal conditions ensure the performance optimization of the material, and the synergistic effect of each step jointly endows the material with efficient and stable catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 (a) SEM image and (b) TEM image of NiBDC prepared in Comparative Example 1;
[0026] Figure 2 NiBDC@NiS prepared in Example 1 0.68 (a) SEM images, (b) TEM images, (c) high-angle annular dark-field SEM images, and (d) AFM images;
[0027] Figure 3 Transmission electron microscopy and high-resolution transmission electron microscopy images of different nickel-related catalysts, (a1) NiBDC@NiS 0.14 Transmission electron microscopy image, (a2) NiBDC@NiS 0.68 Transmission electron microscopy image, (a3) NiBDC@NiS 1.28 Transmission electron microscopy image, (b1) NiBDC@NiS 0.14 High-resolution transmission electron microscopy image, (b2) NiBDC@NiS 0.68 High-resolution transmission electron microscopy image, (b3) NiBDC@NiS 1.28 High-resolution transmission electron microscopy images;
[0028] Figure 4 (a) X-ray diffraction patterns, (b) infrared images, (c) Raman images, and (d) Ni and S content images of different nickel-related catalysts;
[0029] Figure 5(a) OER linear sweep voltammograms of different nickel-related catalysts in 1.0M KOH electrolyte, (b) BOR linear sweep voltammograms in 1.0M KOH+0.1M BDO electrolyte;
[0030] Figure 6 (a) Tafel slope diagram and (b) electrochemical impedance spectroscopy of different nickel-related catalysts in 1.0M KOH+0.1M BDO electrolyte;
[0031] Figure 7 NiBDC@NiS prepared in Example 1 0.68 (a) Electrochemical impedance spectroscopy of the catalyst at different potentials in 1.0M KOH+0.1M BDO electrolyte, (b) Electrochemical impedance spectroscopy of the catalyst at different potentials in 1.0M KOH electrolyte;
[0032] Figure 8 The catalyst NiBDC@NiS prepared in Example 1 0.68 (a) H-NMR spectrum of the electrolysis products of 1,4-butanediol, (b) HPLC chromatograms of different transferred charge numbers;
[0033] Fig. 9 This is the H-NMR spectrum of the hydrolysis product of PBS waste;
[0034] Fig.10 The reaction pathway for the oxidation of 1,4-butanediol to succinate in alkaline medium. DETAILED DESCRIPTION
[0035] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0036] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents in the art. Nickel foam (thickness 1.7 mm, Ni purity> 99.5%) was purchased from Lizhiyuan Battery Sales Department, Yingze District, Taiyuan City; graphite rod (C303) and mercury / mercuric oxide electrode (R0501) were purchased from Tianjin Aida Hengsheng Technology Development Co., Ltd.; PBS (150 mesh) was purchased from Guangdong Hengfa Plastic Technology Co., Ltd.
[0037] Example 1
[0038] A thiol-modified nickel MOF nanosheet array material and a preparation method thereof, wherein the preparation process is as follows:
[0039] 145 mg of nickel chloride hexahydrate, 83 mg of terephthalic acid and 8.6 mg of 1,4-benzenedimethanethiol were dissolved in 18 mL of DMF mixed solution (the volume ratio of DMF, deionized water and ethanol was 16:1:1), and stirred to form a uniform reaction solution (the mass volume ratio of nickel chloride hexahydrate, terephthalic acid, 1,4-benzenedimethanethiol and DMF mixed solution was 33.7 mg:19.3 mg:2 mg:4.18 mL). A clean piece of nickel foam (0.33 g) was taken, soaked in the reaction solution, placed in a reactor together, and hydrothermally reacted at 150 ° C for 6 h. After the reaction was completed, it was rinsed with water and ethanol respectively, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain a nickel MOF material loaded on nickel foam, that is, a thiol-modified nickel MOF nanosheet array material, named NiBDC@NiS loaded on nickel foam 0.68 .
[0040] Example 2
[0041] Compared with Example 1, most of the contents are the same, except that the mass of the nickel chloride hexahydrate is adjusted to 25 mg.
[0042] Example 3
[0043] Compared with Example 1, most of the contents are the same, except that the mass of the nickel chloride hexahydrate is adjusted to 40 mg.
[0044] Example 4
[0045] Compared with Example 1, most of the conditions are the same, except that the mass of terephthalic acid is adjusted to 15 mg.
[0046] Example 5
[0047] Compared with Example 1, most of the conditions are the same, except that the mass of terephthalic acid is adjusted to 25 mg.
[0048] Comparative Example 1
[0049] A nickel MOF nanosheet array material and a preparation method thereof, compared with Example 1, most of them are the same, except that the 1,4-benzenedimethanethiol is not added, and the preparation process thereof is:
[0050] 145 mg of nickel chloride hexahydrate and 83 mg of terephthalic acid were dissolved in 18 mL of DMF mixed solution (the volume ratio of DMF, deionized water and ethanol was 16:1:1), and stirred to form a uniform reaction solution (the mass volume ratio of nickel chloride hexahydrate, terephthalic acid and DMF mixed solution was 33.7 mg:19.3 mg:4.18 mL). A clean piece of nickel foam (0.33 g) was taken, soaked in the reaction solution, placed in a reactor together, and hydrothermally reacted at 150 ° C for 6 h. After the reaction was completed, it was rinsed with water and ethanol respectively, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain a nickel MOF material loaded on nickel foam, that is, a nickel MOF nanosheet array material, named NiBDC loaded on nickel foam.
[0051] Comparative Example 2
[0052] A thiol-modified nickel MOF nanosheet array material and a preparation method thereof are mostly the same as those in the embodiment, except that the amount of 1,4-benzenedimethanethiol added is different. The preparation process is as follows:
[0053] 145 mg of nickel chloride hexahydrate, 83 mg of terephthalic acid and 4.3 mg of 1,4-benzenedimethanethiol were dissolved in 18 mL of DMF mixed solution (the volume ratio of DMF, deionized water and ethanol was 16:1:1), and stirred to form a uniform reaction solution (the mass volume ratio of nickel chloride hexahydrate, terephthalic acid, 1,4-benzenedimethanethiol and DMF mixed solution was 33.7 mg:19.3 mg:1 mg:4.18 mL). A clean piece of nickel foam (0.33 g) was taken, soaked in the reaction solution, placed in a reactor together, and hydrothermally reacted at 150 ° C for 6 h. After the reaction was completed, it was rinsed with water and ethanol respectively, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain a nickel MOF material loaded on nickel foam, that is, a thiol-modified nickel MOF nanosheet array material, named NiBDC@NiS loaded on nickel foam 0.14 .
[0054] Comparative Example 3
[0055] A thiol-modified nickel MOF nanosheet array material and a preparation method thereof are mostly the same as those in the embodiment, except that the amount of 1,4-benzenedimethanethiol added is different. The preparation process is as follows:
[0056] 145 mg of nickel chloride hexahydrate, 83 mg of terephthalic acid and 12.9 mg of 1,4-benzenedimethanethiol were dissolved in 18 mL of DMF mixed solution (the volume ratio of DMF, deionized water and ethanol was 16:1:1), and stirred to form a uniform reaction solution (the mass volume ratio of nickel chloride hexahydrate, terephthalic acid, 1,4-benzenedimethanethiol and DMF mixed solution was 33.7 mg:19.3 mg:3 mg:4.18 mL). A clean piece of nickel foam (0.33 g) was taken, soaked in the reaction solution, placed in a reactor together, and hydrothermally reacted at 150 ° C for 6 h. After the reaction was completed, it was rinsed with water and ethanol respectively, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain a nickel MOF material loaded on nickel foam, that is, a thiol-modified nickel MOF nanosheet array material, named NiBDC@NiS loaded on nickel foam 1.28 .
[0057] The NiBDC and NiBDC@NiS prepared above were loaded on nickel foam. 0.14 、NiBDC@NiS 0.68 、NiBDC@NiS 1.28 The following characterization and performance tests were performed:
[0058] (1) Characterization:
[0059] Figure 1 The scanning electron microscope image of NiBDC ( Figure 1 (a)) and transmission electron microscopy images ( Figure 1 (b)), as can be seen from the figure, NiBDC shows a two-dimensional randomly oriented ultrathin smooth nanosheet morphology.
[0060] Figure 2 NiBDC@NiS 0.68 SEM images of Figure 2 (a))、TEM image( Figure 2 (b)), high-angle annular dark field scanning transmission electron microscopy image ( Figure 2 (c)) and atomic force microscopy images ( Figure 2 (d)), it can be seen from the figure that NiBDC@NiS 0.68 It also presents a smooth nanosheet morphology, indicating that the introduction of a small amount of thiol maintains the morphology of the nanosheet, but NiS nanoclusters are generated on the surface of the nanosheet.
[0061] Figure 3 Transmission electron microscopy images and high-resolution transmission electron microscopy images of different nickel-related catalysts. Figure 3 (a1) and Figure 3 (b1) is NiBDC@NiS 0.14 , Figure 3 (a2) and Figure 3(b2) is NiBDC@NiS 0.68 , Figure 3 (a3) and Figure 3 (b3) is NiBDC@NiS 1.28 , it can be seen that the more thiol is added, the more NiS nanoclusters are produced.
[0062] Figure 4 For NiBDC, NiBDC@NiS 0.14 、NiBDC@NiS 0.68 、NiBDC@NiS 1.28 X-ray diffraction pattern of Figure 4 (a))、Infrared image( Figure 4 (b)), Raman map ( Figure 4 (c)) and Ni, S content comparison chart ( Figure 4 (d)), where the infrared and Raman images show that there are no other functional groups and vibration peaks, indicating the successful synthesis of MOF. The X-ray diffraction spectrum and the comparison of Ni and S content also show that as the amount of thiol increases, the S content also increases, causing the XRD peak to shift to a smaller angle.
[0063] (2) NiBDC@NiS 0.68 Electrochemical testing method was performed as a 1,4-butanediol oxidation reaction (BOR) catalyst.
[0064] (2-1) The experimental parameters are as follows:
[0065] The reaction system is a three-electrode system, loaded with different nickel-related catalysts (NiBDC, NiBDC@NiS 0.14 、NiBDC@NiS 0.68 、NiBDC@NiS 1.28 ) was used as the working electrode, graphite rod as the counter electrode, and mercury / mercuric oxide as the reference electrode.
[0066] Oxygen evolution reaction (OER) tests were performed in 1.0 M KOH solution, and BOR tests were performed in 1.0 M KOH solution containing 0.1 M 1,4-butanediol. BOR tests were performed in PBS hydrolyzate.
[0067] The scanning rate of the linear sweep voltammetry (LSV) curve was 10 mV s -1 .
[0068] Before acquiring the electrochemical data, cyclic voltammetry was performed at 100 mV s -1 The working electrode is activated at a scan rate to achieve a stable electrode state.
[0069] The Tafel slope is the slope of the straight line obtained by linear fitting the points in the Tafel plot.
[0070] Electrochemical impedance spectroscopy (EIS) measurements were performed in the frequency range of 1 MHz to 0.1 Hz with an amplitude of 5 mV.
[0071] The catalyst stability was evaluated by galvanostatic chronopotentiometry.
[0072] (2-2)NiBDC@NiS 0.68 Catalytic electrolysis and product detection
[0073] Long-term electrolysis experiments for the oxidation of BDO and the oxidation of PBS hydrolysate were carried out in a three-electrode system at room temperature.
[0074] After the electrolysis, 500 μL of the electrolyte solution was collected and then analyzed by nuclear magnetic resonance (NMR) spectrometer and high performance liquid chromatography (HPLC).
[0075] (2-3)NiBDC@NiS 0.68 BOR performance evaluation of catalysts
[0076] Figure 5 (a) and Figure 5 (b) shows the linear sweep voltammetry curves of different nickel-related catalysts during OER and BOR. It can be seen from the figure that NiBDC@NiS 0.68 The catalyst has a higher anodic current (at 500 mA cm) for BOR than for OER. -2 The voltage at the current density was 1.42 V), indicating that the reaction kinetics of BOR is much faster and confirming the importance of thiol modification.
[0077] Figure 6 (a) and Figure 6 (b) The Tafel plots and electrochemical impedance spectroscopy plots of different nickel-related catalysts during BOR are shown, respectively, indicating that NiBDC@NiS 0.68 The catalyst has faster BOR reaction kinetics, and the diameter of the semicircle curve of the impedance data is the smallest, indicating faster interfacial charge transfer and faster kinetics.
[0078] Figure 7 (a) NiBDC@NiS 0.68 The electrochemical impedance spectra of the catalyst at different potentials in 1.0M KOH+0.1M BDO electrolyte show that as the potential increases, the impedance data gradually changes from a straight line to a semicircular curve, indicating that BOR occurs. And as the potential increases, the radius of the semicircular curve decreases, indicating that the impedance of BOR decreases and the reaction kinetics accelerates. Figure 7 (b) NiBDC@NiS 0.68 The electrochemical impedance spectra of the catalyst at different potentials in 1.0M KOH electrolyte show that the semicircular curve only begins to appear at 1.7V in the OER process, while the semicircular curve only appears at 1.4V in the BOR process, which also illustrates the fast reaction kinetics of the BOR process.
[0079] Figure 8 (a) NiBDC@NiS 0.68 The H NMR spectrum of the product was collected after the catalyst electrolyzed 1,4-butanediol for a long time. It can be seen that after a long period of electrolysis, the chemical shift of 1,4-butanediol disappeared at 1.42 and 3.46 ppm, and the peak of succinate appeared at 2.26 ppm, confirming that succinate is the main oxidation product of 1,4-butanediol. Figure 8 (b) Mn d -High performance liquid chromatograms of the products collected under different electrolysis coulomb numbers of the NiNDA catalyst were used to study the intermediates and oxidation products of the BOR process. It can be seen that, except for the 4-hydroxybutyric acid (HBA) intermediate, only succinate was detected in the electrolyte, indicating that succinate was the main oxidation product at a potential of 1.4 V.
[0080] Fig. 9 This is the nuclear magnetic hydrogen spectrum of the hydrolysis product of PBS waste. It can be seen that after alkaline hydrolysis, PBS waste obtained two products: 1,4-butanediol and succinic acid.
[0081] Fig.10 The following is a possible reaction pathway for the oxidation of 1,4-butanediol to formate in alkaline medium. The oxidation of 1,4-butanediol starts with the transfer of 2 electrons to generate 4-hydroxybutyraldehyde, followed by two possible oxidation pathways: one is that the aldehyde group is first oxidized to the intermediate 4-hydroxybutyric acid, and then the alcohol hydroxyl group is oxidized to the final product succinic acid. Pathway II oxidizes the alcohol hydroxyl group to 1,4-butanedialdehyde, and then continues to oxidize to succinic acid.
[0082] In summary, the comparative experimental results of Example 1 of the present invention and Comparative Example 1, Comparative Example 2, and Comparative Example 3 further highlight the creativity of the present invention in catalytic performance. Example 1 not only significantly improves the catalytic activity but also maintains the high stability of the material by introducing thiol groups into the nickel MOF nanosheet array. In contrast, although the nickel MOF without thiol functionalization in Comparative Example 1 has certain catalytic activity, its catalytic efficiency is significantly lower than that of Example 1 due to the lack of electronic structure regulation ability. In Comparative Examples 2 and 3, the catalysts modified with thiol are used, and too little or too much thiol will result in a low exposure rate of the active sites, limited mass transfer efficiency, and the catalytic performance is still inferior to that of Example 1. Therefore, selecting the appropriate amount of thiol is the key point to improve catalytic activity. It is feasible to upgrade PBS waste plastics into high-value-added succinate chemicals through thiol-modified nickel MOF nanosheet array materials. Electrocatalytic refining strategy.
[0083] Specific experimental data show that the catalytic conversion rate and selectivity of Example 1 in the target reaction are significantly better than those of Comparative Examples 1 to 3. This shows that the present invention successfully solves the deficiencies of conventional catalysts in conductivity and catalytic activity through the coordinated design of nanosheet array structure and thiol functionalization, and has significant innovation and application prospects.
[0084] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a thiol-modified nickel MOF nanosheet array material, characterized in that: A nickel salt, terephthalic acid, 1,4-benzenedimethanethiol and a solvent are mixed to obtain a reaction solution; a nickel foam is immersed in the reaction solution for a hydrothermal reaction, and after the reaction is completed, a nickel MOF material loaded on the nickel foam is obtained, namely, a thiol-modified nickel MOF nanosheet array material.
2. The method for preparing a thiol-modified nickel MOF nanosheet array material according to claim 1, characterized in that: The mass volume ratio of the nickel salt, terephthalic acid, 1,4-benzenedimethylenethiol and solvent is 25-40 mg: 15-25 mg: 2 mg: 1-5 mL.
3. The method for preparing a thiol-modified nickel MOF nanosheet array material according to claim 1, characterized in that: The nickel salts include nickel chloride, nickel sulfate and nickel nitrate.
4. The method for preparing a thiol-modified nickel MOF nanosheet array material according to claim 1, characterized in that: The solvent is a DMF mixed solution, which is a mixture of DMF, water and ethanol, and the volume ratio of the three is 10-20:1:0.5-2.
5. The method for preparing a thiol-modified nickel MOF nanosheet array material according to claim 1, characterized in that: The mass volume ratio of the nickel foam to the reaction solution is 10-30 mg:1 mL.
6. The method for preparing a thiol-modified nickel MOF nanosheet array material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 120-180°C.
7. A thiol-modified nickel MOF nanosheet array material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. The thiol-modified nickel MOF nanosheet array material according to claim 7, characterized in that: The nickel MOF material is loaded on nickel foam and presents a nanosheet structure, in which nickel sulfide clusters are loaded on the nanosheet.
9. Application of the thiol-modified nickel MOF nanosheet array material as claimed in claim 7 in the field of electrocatalysis.
10. The use of a thiol-modified nickel MOF nanosheet array material according to claim 9, characterized in that: The nickel MOF nanosheet array material is used as a catalyst for the reaction of oxidizing 1,4-butanediol to generate succinate from the hydrolysis product of PBS.
Citation Information
Patent Citations
Nickel metal organic frame material and preparation method and application thereof
CN110031522A
Nickel-based metal organic framework layered nanosheet array material as well as preparation and application thereof
CN114709086A
Preparation method of sulfur-doped nickel-based metal organic framework electrode material with bionic active domain as well as product and application of sulfur-doped nickel-based metal organic framework electrode material
CN114892212A
Preparation method and application of MOFs nanosheet photocatalyst with methyl mercaptan purification function
CN115283014A
Manganese-doped nickel MOF nanosheet array material as well as preparation method and application thereof
CN117987873A